Virtual Teaching During the COVID-19 Pandemic and the Psychosocial Well-Being of Medical Students at College of Medicine, Jeddah (Medical Forum Monthly, 2023)
Objective: To determine the psychosocial well-being of pandemic hit medical students in Saudi Arabia and get an insight into their experience on virtual learning during the pandemic.Study Design: Observational / cross sectional studyPlace and Duration of Study: This study was conducted at the College of Medicine (COM) (KSAU-HS), Jeddah campus from Oct 21 till Oct 22.Materials and Methods: A total of 844 medical students were included in the study. A sample size of 265 was calculated. Convenience sampling technique was used. An online self-reported questionnaire was adopted from previously published studies to investigate the study objectives. Descriptive statistics were used to describe patients’ demographic characteristics. Categorical data were reported as percentages (frequencies). The statistical analyses were carried out using S.P.S.S. (version 27).Results: More than one third of the study population reported difficulty falling asleep (43.1%), waking up in the middle of night or early morning (32.8%) and anxiety. While only a small proportion (8 %)reported severe anxiety. Ability to record the meeting, access to online material and learning on your own pace were identified as few of the main advantages of virtual classes. While technical problems remained, the main challenge followed by missing human interaction and warmth. Most of the students considered face to face sessions to be highly effective for clinical teachingConclusion: As a result of the pandemic, virtual meetings continued to maintain the cycle of educational activities. The majority of the medical students reported mild to moderate anxiety. Face-to-face teaching was considered an effective tool for enhancing knowledge and a preferred method, particularly when teaching clinical skills. Moreover, they reported that face-to-face sessions were associated with a greater sense of well-being among students